Border Identifications : Narratives of Religion, Gender, and Class on the U.S.-Mexico Border - Vila, Pablo, 1952- (Book collections on Project MUSE., 2005)
"An ethnography that explores the role of religion, gender, and class in the formation of social identity on both sides of the US-Mexico border. A continuation of the study Vila began in Crossing Borders, Reinforcing Borders"--Provided by publisher.